An Extensive Study On Machine Learning Based Routing Algorithms Used In Wireless Sensor Network - Rakesh Kumar (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks (WSNs) play an important role in monitoring some real time dynamic environments that changes rapidly over time domain. The changes in these application areas caused by some environmental factors, which are not possible to controlled by any human made systems. We can only monitor these changes, and that’s why WSN is required. WSN also face some challenges due to dynamic behavior of application area like, resource inhibited, low processing speed, restricted communication bandwidth, and narrow battery power. To acclimate these defies, machine learning techniques must be utilizing to inspire a design methodology for maximum resource utilization and to maximize the lifespan of sensor network. This article offering an extensive review of literature for machine learning methods that were used to discourse common routing level issues faced by WSNs. Scope of this review is limited to the routing mechanism only, and provide a comparative exploration to design routing algorithms based on machine learning approach to mitigate routing challenges and prolong the network lifetime.